Non- Formal Education Efforts to Improve Human Resources in Facing The Challenges of Global Digitalization Through Online Courses - Erlinda Erlinda; Fira Rama Fira Rama Puteri Mahardika; Nurfrida Aulia Tiarani Aulia Tiarani; Nurma Yunita Sari (English Language and Literature International Conference (ELLiC) Proceedings, 2023)
The rapid changes in world civilization in various countries are marked by the unlimited use of information technology. The rapid development of information technology in the digital era makes people need more than just literacy; they need a learning perspective that is able to educate them about the benefits of effective and critical filtering of valid information. To develop abilities and skills, not only can they be achieved through formal education. One of them is a digital-based non-formal learning program that facilitates the community's development in the digitalization era, namely online courses. The research method used is the System Literature Reviewer, or SLR, method. Where in the process do researchers collect, enter, process, and store data? This method aims to solve the problems that researchers have through a literature review of previous journals. Nonformal education provides many options for meeting needs in a digital era; this iS certainly tailored to the needs and circumstances of the community to be addressed. Social society will be studied as the fulfillment of needs occurs so that adjustments to nonformal education methods will increasingly develop. Online learning outcomes are as good or better than conventional learning outcomes. Although it has been found that there are positive outcomes from online learning, it is not certain that this is applicable to all courses. There is no evidence that online learning is superior as a learning medium, which is in line with previous literature.